Teaching grassroots soccer: a systematic review of literature - Alejandro Almonacid-Fierro; Ricardo Souza de Carvalho; Sergio Sepúlveda-Vallejos; Jorge Méndez-Cornejo; Mirko Aguilar-Valdés (IP Iermakov S.S., 2024)
Background and Study Aim. The process of soccer training for children and young people involves systematic exercise over an extended period to build a strong foundation of motor skills. These skills are designed to be both versatile and specific to the sport. The purpose of this research is to conduct a systematic review of literature related to the process of teaching grassroots football. This review aims to contribute to a better understanding of the strategies and methods employed in the development and training of young athletes. Material and Methods. To conduct this review, studies were searched in the Web of Science (WOS) and Scopus databases from 2012 to 2022. The search focused on scientific articles addressing soccer teaching for children and girls up to 14 years old, using the keywords "children AND (football OR soccer) AND teaching." The sample was limited to research in Spanish and English. The search yielded 149 articles, from which 19 studies were selected based on their titles and abstracts. Results. The findings revealed two main categories: teaching methods and their impact on technical and tactical skills in grassroots football, and factors affecting technical-tactical performance in this context. The most significant findings emphasize the importance of a comprehensive approach to teaching grassroots football, which involves the coordination of knowledge, skills, strategies, decision-making, and technical abilities. Conclusions. The review concludes that a variety of teaching approaches should be considered, and methodologies should be constantly evaluated to train future footballers with a deep understanding of the game.